Channels of interprovincial consumption risk sharing in the People's Republic of China - Julan Du; Qing He; Oliver M. Rui (Asian Development Bank Institute (ADBI), 2011)
This paper analyzes consumption risk sharing among provinces in the People's Republic of China (PRC) during 1980 - 2007. The analysis finds that 9.4% of shocks to gross provincial product are smoothed by the interprovincial fiscal transfer system. This system also cushions a relatively large percentage of province-specific shocks in coastal areas. Using a variety of indicators, we explored nonfiscal channels of consumption risk sharing. We found that the migration of rural labor to urban areas and the remittance of migrant wages play an important role in promoting interprovincial consumption risk sharing in inland PRC provinces. In contrast, the extent of risk sharing through financial intermediation and capital markets is very limited. These factors have resulted in a low degree of risk sharing among provinces, especially during the last decade.
Keywords: O16; O53; R11; 330; prc provinces; interprovincial fiscal transfers; consumption risk sharing; Gesamtwirtschaftlicher Konsum; Räumliche Verteilung; Landflucht; Rücküberweisungen; Finanzausgleich; Provinz; China